Photosensitizer, pH sensing and optical limiting properties of BODIPY dyes - May, Aviwe Khanya (Rhodes University, Faculty of Science, Department of Chemistry, 2018)
A series of BODIPY dyes have been successfully synthesised and structurally characterised to examine the effect of halogenation at the 2,6-positions and the introduction of styryl and vinylene groups at the 3,5-positions. The photophysical properties were studied, to assess the effect of the enhancement of the rate of intersystem crossing through halogenation on the fluorescence properties and the generation of reactive oxygen species. This is important in the assessment of the suitability of applying these molecules as photosensitizer dyes for photodynamic therapy and photodynamic antimicrobial chemotherapy. Upon bromination, the dyes showed moderately high singlet oxygen quantum yields. The inclusion of BODIPY dyes into cyclodextrins was explored since it makes them water soluble and hence suitable for biomedical applications, but no singlet oxygen was detected in aqueous media for the inclusion complexes. In order to red-shift the main spectral band of the BODIPY dyes into the therapeutic window, styryl groups were introduced at the 3,5-positions via a modified Knoevenagel condensation reaction. Since the main spectral band lies well above 532 nm, the second harmonic of the Nd:YAG laser, there is relatively weak absorbance at this wavelength. The 3,5-distyryl and 3,5-divinylene BODIPY dyes were assessed for their potential utility for application in nonlinear optics (NLO), and they demonstrated typical nonlinear absorption behaviour characterised by reverse saturable absorption (RSA) in z-scan measurements. Furthermore, the dyes possess excellent optical limiting parameters, such as their third-order suspectibility and hyperpolarizability values, in a wide range of solvents. One dye containing dimethylamino moieties on styryl groups attached at the 3,5-positions was assessed for potential application as an on/off fluorescence sensor. The dye proved to be successful, since intramolecular charge transfer in the S1 state was eliminated in the presence of acid and this results in a fluorescence "turn on" effect. This process was found to be reversible with the addition of a base.
Keywords: Dyes and dyeing -- Chemistry; Halogenation; Photochemotherapy; Bromination; Photosensitizing compounds; Nonlinear optics; BODIPY dyes